Field reports, Robert Cecil, fall 1989 - Cecil, Robert I.et al (1989)
Field Reports for fall 1989 contributed by Robert Cecil with detailed descriptions for some sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed